Effect of birth plans integrated into childbirth preparation classes on maternal and neonatal outcomes of Iranian women: A randomized controlled trial - Mohaghegh, Zaynab; Javadnoori, Mojgan; Najafian, Mahin; Abedi, Parvin; Kazemnejad Leyli, Ehsan; Montazeri, Simin; Bakhtiari, Shahla (Frontiers in Global Women's Health, 2023)
Background: Involvement of women in the decision-making process during childbirth plays an important role in their physical and psychosocial preparation. A birth plan allows the woman to express her expectations and facilitates her participation in her own care. The present study is the first to assess the implementation of birth plans integrated into childbirth preparation classes in Tehran, Iran. Methods: This study is a randomized controlled clinical trial performed on 300 pregnant women at 32-33 weeks of gestation referring to four public health centers in Tehran, Iran. The participants were randomly allocated into intervention and control groups using block randomization method. A training session on the items of the birth plan checklist was held in the fifth session of childbirth preparation classes for the participants in the intervention group. Accordingly, a birth plan was prepared according to the requests of mothers. The birth plan was implemented after the women were admitted to the maternity ward. The primary outcomes were frequency of vaginal birth, mean duration of labor stages, and mean score of childbirth satisfaction. We used a checklist of maternal and neonatal outcomes, Mackey’s childbirth satisfaction questionnaire, and a partogram form for data collection. Independent t-test, Mann–Whitney U-test, Chi-square test, Fisher’s exact test, and logistic regression were used for data analysis. Results: Vaginal birth rates were significantly higher in women who had birth plans compared with those without (81.9% vs. 48.7%, p<0.001). Also, the lengths of the first and the second stages of labor were significantly shorter in women having a birth plan (P = 0.02). Women in the birth plan group were significantly more satisfied with the process of labor and childbearing (P<0.001), and started breastfeeding after birth earlier than those in the control group (p<0.001). Conclusion: Having a birth plan and attending childbirth preparation classes can increase the rate of normal vaginal birth. Also, according to our results, women's participation in the decision- making process and fulfilling their preferences during birth can improve maternal and neonatal outcomes and childbirth satisfaction.